2020
DOI: 10.1111/cup.13783
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of nail lichen planus: A cross‐sectional study

Abstract: Introduction: Up to 10% of patients with lichen planus (LP) have nail involvement; still there is a paucity of studies on histopathological features. Nevertheless, nail biopsy is the diagnostic standard, especially for isolated nail LP. Methodology: Nails of 45 patients with nail LP were evaluated clinically and biopsies taken from most involved nail (25 nail bed and 20 matrix biopsies). Correlation of clinical and histopathological features was also done. Results: The mean age of the study group participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…Most of the patients in the present study (85.7%) had melanonychia. This finding is consistent with a study in India by Kharghoria et al, 4 which reported that 88.9% of their patients had melanonychia. Multiple studies have observed that postinflammatory melanonychia is found with many inflammatory nail disorders, such as nail lichen planus, psoriatic nail, chronic paronychia, and traumatic nail.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the patients in the present study (85.7%) had melanonychia. This finding is consistent with a study in India by Kharghoria et al, 4 which reported that 88.9% of their patients had melanonychia. Multiple studies have observed that postinflammatory melanonychia is found with many inflammatory nail disorders, such as nail lichen planus, psoriatic nail, chronic paronychia, and traumatic nail.…”
Section: Discussionsupporting
confidence: 93%
“… 1 , 2 Approximately 4% of nail lichen planus cases result in permanent nail scarring. 4 The present study showed that 10% of patients with lichen planus had the characteristics of nail lichen planus, which is similar to the findings of earlier investigations. 1 , 2 …”
Section: Discussionsupporting
confidence: 91%
“…Moreover, inflammatory histological findings have been reported on NLP, and these include hypergranulosis of the nail matrix and bed epithelium, sawtooth acanthosis, irregular epidermal hyperplasia, a lichenoid infiltrate with the formation of Civatte bodies, vacuolar degeneration of the basement membrane, and pigmentary incontinence. 19,20 Isolated nail bed involvement in NLP is rarely seen. In our sample, no patient presented with single nail bed involvement; nevertheless, the ultrasound examination showed subclinical findings in multiple nails ("halo sign" and inflammatory signs in the nail bed and proximal nail fold).…”
Section: Discussionmentioning
confidence: 99%
“…The prominent ultrasonographic signs of inflammation surrounding the nail plate origin and involving the nail matrix region can explain why NLP is so destructive of the nail unit and how a clinical pterygium, which implies the presence of scarring, can appear in this entity. Moreover, inflammatory histological findings have been reported on NLP, and these include hypergranulosis of the nail matrix and bed epithelium, sawtooth acanthosis, irregular epidermal hyperplasia, a lichenoid infiltrate with the formation of Civatte bodies, vacuolar degeneration of the basement membrane, and pigmentary incontinence 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…In this issue of our Journal of Cutaneous Pathology , Kharghoria and colleagues 1 present data from a cross‐sectional study of 45 patients with nail unit lichen planus. Biopsy specimens included 25 of the nail bed and 20 of the nail matrix.…”
mentioning
confidence: 99%